GOD’S MERCY OR JONAH’S ANGER? AN ORTHODOX APPROACH TO THE CASE OF NINEVEH - PAȘCA-TUȘA, Stelian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
The Book of the Prophet Jonah challenges us to face a reality that justifies our quality of God’s children. Often, Christians are faced with a choice between creating or not the necessary frameworks for the redemption of the contemporary man who has sometimes an adverse attitude towards the Church. It is this choice that their privileged status of God’s chosen people, of holy people whose mission is to be a light among other people, depends on. Those who set themselves up as judges and punishers of others’ deeds are in conflict with God, by neglecting their vocation and the mission to which they have been called. For these reasons, the association with Jonah is extremely appropriate. The prophet refuses to preach in Nineveh in order to avoid being the instrument by which God brings redemption to an impressive number of sinners. The aim of this study is to fructify this behavioural paradigm to acknowledge the fact that disobedience towards God takes us out of communion and makes us lose the privileged status of God’s chosen one. In order to succeed in this endeavour, I shall bear in mind the most recent researches that try to solve the mystery of the prophet’s unexpected behaviour, but also the opinions of some personalities who represent the Jewish and patristic tradition, which mostly characterises the Christian East. These directions shall offer the reader the possibility of thinking more before choosing to get angry like Jonah or be merciful like God